Self-Perceived Employability in the Digital Era: Analysis of Online Social Support, Social Media User Type, and Career Adaptability - Noviati, Nur Pratiwi; Nu'man, Thobagus Mohammad; Iqbal, Mirza Muchammad; Akmala, Lifthya Ahadiati (Universitas Islam Indonesia, 2024)
Self-perceived employability (SPE) is important for students entering the workforce in the digital era. This study aimed to explore the correlation between online social support (OSS), social media user types (SMUT), and SPE with career adaptability (CAD) serving as a mediator. It also examined the relationship of several covariates such as work experience, international exposure, and organizational experience. A total of 360 students comprising males (19.4%) and females (80.6%) participated voluntarily in this study. The data was further collected using a Likert scale measuring OSS ( = .88), SPE ( = .85), and CAD ( = .86) with eight items for all variables. Furthermore, a five item statement was used to assess SMUT where respondents selected the item most appropriate to the condition. The results of Structural Equation Model (SEM) testing carried out using RStudio with the Lavaan package version 0.6-18 showed that OSS played an important role in improving SPE both directly and through CAD. Although SMUT did not significantly affect SPE through CAD, it suggested a broader impact when considering the total effect. This study further emphasized the importance of fostering OSS to increase career adaptability and eventually improve SPE. Additionally, the results contributed to the literature by providing empirical evidence regarding the factors influencing students’ SPE. Practically, this study could support career development programs focused on student character.